Indeks Gonadosomatik dan Struktur Histologis Gonad Ikan Wader Pari (Rasbora lateristriata Bleeker, 1854) pada Tahap Perkembangan Pra Dewasa dan Dewasa - , SELVI RAHMAWATI, Ardaning Nuriliani, S.Si., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wader pari (Rasbora lateristriata Bleeker, 1854) is a freshwater fish which has been exploited excessively in nature. Hence, information about its proper cultivation technique is important. Reproductive aspect is the most important aspect to develop cultivation technique of fish. This research purposed to study the reproductive aspects of wader pari fish (Rasbora lateristriata Bleeker, 1854), concern in the gonadosomatic index (GSI) and gonadal histological structure of male and female in sub adult and adult developmental stage. Staging was done based on standard lenght which were: sub adult (20-40 mm) dan adult (> 40 mm). Spesimen was dissected, weighed, gonad was taken over and measured for gonadosomatic index. Organ was fixed in NBF 4% for histological preparation using paraffin method. Organ was sliced with 6 Î¼m thickness and stained by Hematoxylin-Eosin. The results were analyzed quantitatively and qualitatively. Quantitative analysis was done using independent t-test included gonadosomatic index data. Qualitative analysis consisted of descriptive and comparative analysis which included male and female gonadal histological structure observation. The results showed that in the same stage, there were differences between male and female gonadosomatic index. Besides, in different developmental stage, there were no significant GSI differences between sub adult and adult male. On the other hand, there were significant GSI differences between sub adult and adult female. The results of histological structure observation showed that there were gonadal histological structure differences of male wader pari fish (R. lateristriata) in both developmental stage. The differences included composition of spermatogenic cells in seminiferous tubules. Whereas in female wader pari fish (R. lateristriata), the differences included oocytes diameter and composition. From the results, it could be concluded that there were differences in both gonadosomatic index and gonadal histological structure of wader pari fish (Rasbora lateristriata Bleeker, 1854) in sub adult and adult developmental stage.